"Nanny State" Politics: Causal Attributions About Obesity and Support for Regulation. Issue 2 (March 2018) - Haider-Markel, Donald P.; Joslyn, Mark R.
We posit that individuals develop causal stories to explain the world around them, including events, behaviors, and conditions in society. These are narratives that attribute causes to controllable components, such as individual choices, or uncontrollable components, such as broader forces in the environment. We use attribution theory to understand how group identity and individual characteristics may shape causal attributions about obesity. Based on previous empirical findings, we argue that attributions and identity can explain policy preferences. We test our hypotheses using individual-level data from a unique national survey of American adults. Our findings suggest that partisan and weight identities predispose people to make certain attributions about obesity, and these attributions influence policy preferences related to obesity. We suggest policymakers need to consider public attributions about obesity and future research should develop more refined measures of attributions.